Students' attitudes towards learning Arabic language at religious schools in Malaysia: secondary level in Selangor as an example - Zakaria, Abdul Wahab; Mustapha, Maziah (s.n, 2012)
This study aims to identify problem faced by students in learning and understanding Arabic language. The problem encompass students relationships, attitudes and their interests towards learning the Arabic language. In addition, the study also aims to determine to what extent the role teachers and other contributing factor that could have inadvertently aggravated the student's attitudes towards their learning process of Arabic language. For this purpose, the study has employed a descriptive approach in analyzing the data generated from the field. The research finding of the study would indirectly be beneficial particularly to those who are responsible in planning and strengthening the existing teaching and learning Arabic language curriculum. Thus, the overall input from the research finding would eventually help the Arabic teachers in particular to strengthen their teaching and learning approach towards the Arabic language